Relationship among Testicular, Physical and Semen Quality Parameters of Murrah Buffalo Breeding Bulls - Yadav, S K (Indian Journal of Dairy Science, 2017)
Association among physical (Body condition score and rump fat thickness), testicular (scrotal circumference, testicular covering thickness and scrotal surface temperature gradient) and semen quality (ejaculate volume, mass motility, sperm concentration, sperm motility, viability and sperm abnormality) parameters of Murrah buffalo breeding bulls, was studied. For this, 130 mature Murrah buffalo breeding bulls, which were in regular semen collection, were selected from five different centres located in Haryana and Punjab and 4 ejaculates of each bull were evaluated. The bull’s parameters viz. body condition score (BCS), scrotal circumference (SC) and scrotal surface temperature gradient (SSTG) in 130 bulls, and rump fat thickness (RFT) and testicular covering thickness (TCT) of 38 bulls was measured. BCS (1-5) of each bull was recorded by visual observation and palpation, SC was measured using measuring tape (cm), TTC and RFT were measured using ultrasonography (mm) and scrotal surface temperature was recorded (0C) using infrared camera. Semen quality attributes viz. ejaculate volume (EV, ml), mass motility (MM, 0-5), sperm concentration (SPC, million/ml), sperm motility (SM, %), viability (%) and sperm abnormality (SA, %) of each ejaculate were recorded with standard procedure. Results showed that BCS was positively correlated with RFT (r=0.604) (P<0.01) and SC (r=0.201) (P<0.05), whereas, negatively (P<0.05) with SSTG (r=-0.177). Scrotal circumference of bulls had significant (P<0.01) positive correlation with TCT (r=0.441), EV (r=0.352), MM (r=0.293), SM (r=0.261), viability (r=0.277) and RFT(r=0.343) (P<0.05). A positive correlation (r=0.549) (P<0.01) between TCT and RFT was also obtained. Whereas, SSTG was negatively correlated with SA (r= -0.169) and positively with MM (r=0.298) (P<0.01) and SPC (r= 0.201) (P<0.05). It can be concluded that these bull’s parameters were correlated to each other in which scrotal circumference and scrotal surface temperature gradient showed significant positive correlation with semen quality attributes.